Analysis of Motivational Forms in the Poetry of Johann Wolfgang von Goethe - Chatrine Nahampun; Ahmad Bengar Harahap (PT FORMOSA CENDEKIA GLOBAL, 2024)
The aim of this research is to analyze the motivational values in Johann Wolfgang von Goethe's poetry. The method used in this research is a qualitative descriptive method. Hierarchy theory is used to discuss and analyze motivation in these poems. The Miles and Hubermann method was used for techniques and data collection in this research. In this research, the author found 5 motivational values in Johann Wolfgang's poetry, each of which has its own characteristics. These motivational values consist of basic or physiological needs (6 Lyrics), the need for security (12 Lyrics), social needs (5 Lyrics), the need to gain appreciation (11 Lyrics), and the need to actualize oneself (14 Lyrics).